DECENTRALIZATION OF HEALTH SERVICES IN ROMANIA - Ionel DIDEA; Daniela PIRVU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This paper aims to provide an analytical framework for decentralization of health services in Romania. Decentralization, intended as a measure to increase quality of health services provided to the population, and to a better functioning of these some health units far not led to the expected results.